2018
DOI: 10.1039/c8cp00544c
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier mobility of disordered organic semiconductors with correlated energetic and spatial disorder

Abstract: Low charge carrier mobility is one key factor limiting the performance and applicability of devices based on organic semiconductors. Theoretical studies on mobility using the kinetic Monte Carlo or master equation are mainly based on a Gaussian energetic disorder and regular cubic lattices. The dependence of mobility on the electric field, temperature and charge carrier density is well studied for the Gaussian disorder model. In this work, we investigate the influence of spatially correlated site energies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 64 publications
5
48
0
Order By: Relevance
“…Using this correlation mechanism, we have shown that a high correlation in the site energies gives rise to filamentary structures of the local currents [39]. For distances below 2 nm, the correlation function obtained by atomistic simulations [73] has been reproduced with our mechanism, while for long-range hopping, other procedures, e.g., a dipole-based correlation [36], give better results.…”
Section: Scaling Of the Site Energiesmentioning
confidence: 69%
See 3 more Smart Citations
“…Using this correlation mechanism, we have shown that a high correlation in the site energies gives rise to filamentary structures of the local currents [39]. For distances below 2 nm, the correlation function obtained by atomistic simulations [73] has been reproduced with our mechanism, while for long-range hopping, other procedures, e.g., a dipole-based correlation [36], give better results.…”
Section: Scaling Of the Site Energiesmentioning
confidence: 69%
“…We present a simple weighted average approach in Section 3.2. The Voronoi tessellation and the correlation procedure have been discussed recently in more detail [39]. As they are part of our generalized kMC model, we provide a concise summary.…”
Section: Kmc Framework For Organic Materials and Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…[30][31][32] Furthermore, models based on continuum approaches are not sufficient to describe the spatial and energetic disorders, [33] as well as the impact of Coulomb correlation, [34] especially when time-dependent processes are to be investigated. OSC device models have emerged to simulate current-voltage characteristics, [37,38] the effect of blend morphology, [39,40] charge mobility extractions, [41,42] as well as CP separation, [30,[43][44][45][46][47][48] and its competing process, geminate recombination. [35] The kinetic Monte Carlo (kMC) method is a powerful simulation technique to model the time-dependent behavior of physical systems.…”
Section: Wwwadvtheorysimulcommentioning
confidence: 99%